Reopening of dental clinics during SARS-CoV-2 pandemic: an evidence-based review of literature for clinical interventions - Seied Omid Keyhan; Hamid Reza Fallahi; Amin Motamedi; Vahid Khoshkam; Paymon Mehryar; Omid Moghaddas; Behzad Cheshmi; Parsa Firoozi; Parisa Yousefi; Behzad Houshmand (SpringerOpen, 2020)
Abstract Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes serious acute respiratory diseases including pneumonia and bronchitis with approximately 2.3% fatality occurrence. Main body This study argues the main concepts that need to be considered for the gradual reopening of dental offices include treatment planning approaches, fundamental elements needed to prevent transmission of SARS-CoV-2 virus in dental healthcare settings, personal protection equipment (PPE) for dental health care providers, environmental measures, adjunctive measures, and rapid point of care tests in dental offices. Conclusion This article seeks to provide an overview of existing scientific evidence to suggest a guideline for reopening dental offices.